Consider the following function. f(x) = 2x + 5. Place the steps for finding f-1 (x) in the correct order. A. x-2/5= y B. y = 2x + 5 C. y-5 = 2x D. X-5/2=y E. f-1(x) = x-5/2 F.x= 2y+ 5 G. x-5= 2y H. f-1(x) = x-2/5
![Consider the following function fx 2x 5 Place the steps for finding f1 x in the correct order A x25 y B y 2x 5 C y5 2x D X52y E f1x x52 Fx 2y 5 G x5 2y H f1x x2 class=](https://us-static.z-dn.net/files/d62/814603add2e9e20296f454d04c0cc4a0.jpg)
Answer:
[tex]\boxed{\sf \ \ f^{-1}(x)=\dfrac{x-5}{2} \ \ }[/tex]
Step-by-step explanation:
hello,
the easiest way to understand what we have to do is the following in my opinion
we can write
[tex](fof^{-1})(x)=x\\<=>f(f^{-1}(x))=x\\<=>2f^{-1}(x)+5=x\\<=>2f^{-1}(x)+5-5=x-5 \ \ \ subtract \ \ 5\\<=> 2f^{-1}(x)=x-5 \\<=> f^{-1}(x)=\dfrac{x-5}{2} \ \ \ divide \ by \ 2\\[/tex]
so to follow the pattern of your question
y = 2x + 5
we need to find x as a function of y, so let's swap x and y
x = 2y + 5
then subtract 5
x - 5 = 2y
then divide by 2
[tex]\dfrac{x-5}{2}=y[/tex]
finally
[tex]f^{-1}(x)=\dfrac{x-5}{2} \\[/tex]
hope this helps
Answer:
1. y= 2x + 5
2. x = 2y + 5
3. x - 5 = 2y
4. (x-5)/2 =u
5. f^-1(x) = (x-5)/2
Step-by-step explanation:
:)